METAPHOR OF WAR IN POLITICAL DISCOURSE - Mikhailovich Amatov, Alexander; Petrovich Sedykh, Arkadiy; Nikolajevna Ivanishcheva, Olga; Viktorovna Bolgova, Elena; Sergeevna Bolgova, Natalia; Ivanovna Vorobyova, Olga (Revista Inclusiones, 2020)
In modern political communication, one of the main tasks is the formation of a character of a politician aimed at creating a certain image. This image can be either positive and attractive to society, which is a key tool when influencing the mass consciousness or contributing to the advancement of one’s goals, or negative, which is often used by a politician to discredit an opponent due to fierce competition and political struggle. The main informative function of the media in the modern information society is changing the nature of its impact, gaining a manipulative function. A metaphor acts as one of the tools of manipulative impact on the audience. The active use of metaphors in political discourse is due to its ability to influence almost every stage of solving problems in the political sphere: understanding the problem situation, searching for solutions to it, evaluating alternatives and choosing an option.